2012
DOI: 10.5897/jnbh11.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interaction between eye-hand dominance on dart skill

Abstract: The purpose of this research was surveying the effect of interaction between eye hand dominance on dart skill. Twenty healthy male subjects (age: 21.43±1.33) from University of Shahid Chamran were served as the participants for this study. Subjects were divided into two groups: unilateral (right eye and right hand or left eye and left hand) group (10 subjects) and cross lateral (right eye and left hand or left eye and right hand) group (10 subjects). Each group trained for 12 sessions in the same condition. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
(9 reference statements)
0
6
1
Order By: Relevance
“…Regarding the variations in the target, two studies indicated that any object could be used as a target, and while Razeghi (2012) did not indicate the distance between the target and the subject, Laborde et al (2009) , following Buxton & Crosland (1937) protocol, specified a minimum distance of 2 m between target and subject. Dalton, Guillon & Naroo (2015) used a specific chart developed at the Michel Guillon vision clinic, which is scalable at any distance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the variations in the target, two studies indicated that any object could be used as a target, and while Razeghi (2012) did not indicate the distance between the target and the subject, Laborde et al (2009) , following Buxton & Crosland (1937) protocol, specified a minimum distance of 2 m between target and subject. Dalton, Guillon & Naroo (2015) used a specific chart developed at the Michel Guillon vision clinic, which is scalable at any distance.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding variations in the pointing technique, three of the studies ( Sugiyama & Lee, 2005 ; Dalton, Guillon & Naroo, 2015 ; Mann, Runswick & Allen, 2016 ) used a finger (index or thumb) on both arms alternately to reduce the interference with handedness; this procedure was reported by Porac & Coren (1976) . The studies from Razeghi (2012) and Laborde et al (2009) , both studying precision sports (darts and archery), used the index finger of a single hand to point; this single-handed procedure was validated by Lora, Heilman & Roth (2002) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the ability of the visual system to coordinate information received by the eye, then control, guide, and direct the mind and hands to complete certain tasks such as doing basketball technical skills. To know one's literality pattern (dominance of eye, hand, and foot) makes it possible to suggest situations adapted for learning skills more efficiently, to detect and guide young talents, to optimize the work of limbs for each side of the body and to acheive powerful coordination [28]. EHC plays a pivotal role in many kinds of sports, especially in ball games wich require a lot of reaching and catching [29].…”
Section: Discussion There Is No Difference In the Effect Of Part Tmentioning
confidence: 99%
“…On the contrary, in sports without ball, which require aiming skills e.g. archery or darts (Dart skills) recent findings (Laborde, Dosseville, Leconte, & Margas, 2009;Razeghi, Shafie, EFTHYMIOS ZIAGKAS, ALEXANDROS MAVVIDIS, GEORGE GROUIOS, ATHANASIOS LAIOS --------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------- Shebab, & Maleki, 2012) demonstrate that athletes with ipsilateral eye hand dominance have the advantage. The present study does not confirm this view, because we found no significant differences between ipsilateral or contralateral eye-hand dominance groups leading us to conclude that the ipsilateral eye hand dominance gives no advantage in tennis serve performance.…”
Section: Discussionmentioning
confidence: 99%